Synthesis, Structural, and Optical Properties of 2-(2-methyl 8-hydroxyquinoline) Magnesium Nanorods for Optical Display Systems - Suchitra, J. P.; Rhoda, J. Christina; Bharathi Devi, V.; Divya, P.; Albert, Helen Merina (Journal of fluorescence, 2025)
Organic semiconductors find widespread applications in the realm of organic light-emitting diodes (OLEDs) as well as organic photovoltaic cells. In the domain of OLED devices, it is plausible for nano-based Mg metal complexes to play a role as electron and hole-transport layers. In the present investigation, we synthesized 2(2-methyl 8-hydroxyquinoline) magnesium [Mg(mq) 2 ] nanorods through the employment of the precipitation method, using 2-methyl 8- hydroxyquinoline and magnesium acetate. We employed various techniques to characterize the Mg(mq) 2 nanorods, including powder XRD, FTIR spectroscopy, SEM, EDX, UV-Vis, and PL spectroscopy studies. The structural aspects of Mg(mq) 2 were ascertained through P-XRD analysis. The elemental composition of Mg(mq) 2 and its surface texture were established via EDX and HR-SEM analyses. FTIR spectroscopy confirmed the existence of functional groups within the sample. UV-Vis spectroscopy was utilized to evaluate the optical absorbance, bandgap, and Urbach energy of Mg(mq) 2 . The luminescence properties of the Mg(mq) 2 nanorods were determined from the photoluminescence study. The characterization results were compared with the Zn(mq) 2 nano samples. The experimental results presented herein serve to demonstrate the practicality of employing Mg(mq) 2 nanorods in OLED devices.